Isolation and anticancer evaluation of mangostin from garcinia malaccensis - Bakhtiar, M. Taher; Mohamed, Farahidah (IIUM, 2011)
Garcinia malaccensis Hk.f (Guttiferae) is closely resembled to G. mangostana and G. hombroniana. The genus of Garcinia is well known as a medicinal plant in South-east Asia. The research investigated chemical constituents from the stembark of G. malaccensis together with their cytotoxic activity against human cancer cell lines. Purification was carried out by chromatography technique on silica gel and the structures were established by various spectroscopic techniques. MTT assay and trypan blue exclusion method was performed to study cytotoxic activity of the compounds. The phytochemical study led to the isolation of -mangostinandcycloart-24-en-3-ol. -mangostin exhibited a significant cytotoxicity against human oral cancer (HSC-3) cells with an IC50 of 0.33 M. β- and α-mangostin significantly inhibited the proliferation of human chronic myelogenous leukemia (K562) cells with IC50 of 0.40 M and 0.48 M, respectively. However, none of the compounds exhibited activity against human non-small lung carcinoma (H1299) cells.